Changes in urinary 8-hydroxydeoxyguanosine levels during heptathlon race in professional female athletes - Abdel Samia, B. A.; Youssef, G. A. (Journal of Human Kinetics, 2014)
Acute strenuous exercise can induce a state of oxidative stress affecting the involved muscles. Heptathlon is a multi-event exercise of two days duration and can be considered an acute, intensive endurance exercise. The purpose of this study is to compare the oxidative stress response to heptathlon events day by day and to determine the impact of this type of exercise on oxidative stress biomarkers. The study subjects included eight heptathlon athletes who participated in the National First Class Republic competition in Egypt (October 19-21, 2011). Blood samples were collected at rest after exercise for two successive days and analyzed for malondialdehyde (MDA). Morning urine samples were collected one hour after exercise for each day and were analyzed for 8-hydroxydeoxyguanosine (8-OHdG). Results revealed a significant increase (p<0.05) in both plasma MDA and urine 8-OHdG levels after exercise regardless of the day. We concluded that exercise generates higher MDA levels compared to DNA strand breaks and oxidative DNA damage in athletes with antioxidant supplementation.